PENGARUH MOBILE BANKING SERVICE DAN DIGITAL MARKETING TERHADAP CONSUMER LOYALTY MELALUI BRAND TRUST PADA PT BANK NEGARA INDONESIA CABANG CIBINONG - Hairunnisa; Widyastuti, Sri; Thalib, Supriyadi (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
PENGARUH MOBILE BANKING SERVICE DAN DIGITAL MARKETING TERHADAP CONSUMER LOYALTY MELALUI BRAND TRUST PADA PT BANK NEGARA INDONESIA CABANG CIBINONG Hairunnisa1, Sri Widyastuti2, Supriadi Thalib3 Sekolah Pascasarjana Universitas Pancasila123 nisabrghairunnisa77@gmail.com Customer loyalty is the peak achievement of banking business players. Satisfied and loyal customers will not hesitate to become spreaders of good news who always spread the goodness of the banking products they consume. This study aims to determine the effect of mobile banking services and digital marketing on brand trust, to determine the effect of mobile banking services and digital marketing on consumer loyalty and to determine the effect of brand trust on consumer loyalty. This type of research used in this study is causality research. While the research method used in this study is the verification method. The research results obtained are Mobile Banking Service has a positive effect on Customer Loyalty, digital marketing has a positive effect on brand trust, Mobile Banking Service has a positive effect on Customer Loyalty, Digital Marketing has a positive effect on Customer Loyalty and Brand Trust has a positive effect on Customer Loyalty. Keywords: Mobile Banking Service, Digital Marketing, Brand Trust, Consumer Loyalty.